(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the analysis of organization structure of the orthodox monasteries in the Poltavskaya diocese is made on the base of the official church periodicals; their activity trends are characterized; the problems of the monasteries functioning since the 17th till the beginning of the 20th century are determined.